2015
DOI: 10.2147/ndt.s93657
|View full text |Cite
|
Sign up to set email alerts
|

The low level of understanding of depression among patients treated with antidepressants: a survey of 424 outpatients in Japan

Abstract: BackgroundWe used self-administered questionnaires to investigate the level of understanding of depression among outpatients who were administered antidepressants.MethodsA total of 424 outpatients were enrolled in this study. We used an original self-administered questionnaire that consisted of eight categories: (A) depressive symptoms, (B) the course of depression, (C) the cause of depression, (D) the treatment plan, (E) the duration of taking antidepressants, (F) how to discontinue antidepressants, (G) the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
0
5
0
1
Order By: Relevance
“…Because the actual rate of administration of psychoeducation for patients with depression and the level of understanding of depression among patients with depression had not been deeply examined, we previously surveyed the understanding of depression of outpatients who had experienced or were experiencing a depressive episode and who had taken or were taking antidepressants. 22 Low levels of understanding of depression by patients were revealed in our previous study, and the secondary results of the study showed the understanding of depression, which was evaluated using several questionnaires, was significantly associated with the severity of depression. 23 …”
Section: Introductionmentioning
confidence: 69%
“…Because the actual rate of administration of psychoeducation for patients with depression and the level of understanding of depression among patients with depression had not been deeply examined, we previously surveyed the understanding of depression of outpatients who had experienced or were experiencing a depressive episode and who had taken or were taking antidepressants. 22 Low levels of understanding of depression by patients were revealed in our previous study, and the secondary results of the study showed the understanding of depression, which was evaluated using several questionnaires, was significantly associated with the severity of depression. 23 …”
Section: Introductionmentioning
confidence: 69%
“…In the present study, we reanalyzed data from a previous study22,23 to investigate the difference between male and female patients in terms of depression comprehension and showed the effect of psychoeducation. Compared with male patients, female patients with depression showed lower levels of depression comprehension and did not receive adequate psychoeducation from their physicians in the typical treatment course.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, psychoeducation is important for patients with depression, and there are sex differences in depression. Because the prevalence of psychoeducation and level of depression comprehension among patients had not been examined in detail, we evaluated depression comprehension in patients with depressive episodes or with experience of depressive episodes as well as in those who had taken or were taking antidepressants in a previous study 22. We found low levels of depression comprehension among patients, and several questionnaires that evaluated depression comprehension were found to be significantly associated with the severity of depression in the secondary results 22,23…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Accordingly, in a previous study, we assessed the understanding of depression among outpatients who had experienced or were experiencing a depressive episode and who had taken or were taking antidepressants. 11 In that study, Kudo et al found low levels of understanding of depression among patients, and in a secondary analysis, several questionnaires that evaluated patients’ understanding of depression were significantly associated with the severity of depression (Tomita et al, accepted).…”
Section: Introductionmentioning
confidence: 98%